Effect of Lidocaine and Epinephrine on Human Erythrocyte Shape and Vesiculability of Blood Cells - Tanja Slokar; Carlos Lopez-Mariscal; Judita Lea Krek; Roman Štukelj; Oskar Zupanc; Veronika Kralj-Iglič (Advances in Condensed Matter Physics)
The effect of local anesthetic composed of lidocaine and epinephrine on vesiculability of blood cells and erythrocyte shape was studied. Whole blood and plasma were incubated with lidocaine/epinephrine. Extracellular vesicles were isolated by centrifugation and washing and counted by flow cytometry. Lidocaine/epinephrine and each component alone were added to diluted blood. Shape changes were recorded by micrographs. An ensemble of captured frames was analyzed for populations of discocytes, echinocytes, and stomatocytes by using statistical methods. Incubation of whole blood and blood plasma with lidocaine/epinephrine considerably increased concentration of extracellular vesicles in isolates (for an average factor 3.4 in blood and 2.8 in plasma). Lidocaine/epinephrine caused change of erythrocyte shape from mainly discocytic to mainly stomatocytic (higher than 50%). Lidocaine alone had even stronger stomatocytic effect (the percent of stomatocytes was higher than 95%) while epinephrine had echinocytic effect (the percent of echinocytes was higher than 80%). The differences were highly statistically significant p<10-8 with statistical power P=1. Lidocaine/epinephrine induced regions of highly anisotropically curved regions indicating that lidocaine and epinephrine interact with erythrocyte membrane. It was concluded that lidocaine/epinephrine interacts with cell membranes and increases vesiculability of blood cells in vitro.